Aeroelastic instability and wind-excited response of complex lighting poles and antenna masts. (15th February 2015) - Nguyen, Cung Huy; Freda, Andrea; Solari, Giovanni; Tubino, Federica
Highlights: Analytical and experimental investigations are presented. Aeroelastic stability and wind-excited response are evaluated. Aerodynamic eccentricities, upper vibration modes and modal coupling are considered. An application to a real complex antenna mast structure is presented. Critical aspects of the behaviour of lighting poles and antenna masts are shown. Abstract: This paper presents analytical and experimental investigations aimed at evaluating the aeroelastic instability and wind-excited response of slender vertical cantilever structures, in particular complex lighting poles and antenna masts with distributed eccentricities. The application of the methods herein presented to a real structure emphasizes the significance of aerodynamic eccentricities, upper vibration modes and coupling between the translational components of the motion. In such a framework, particular sets of the parameters and specific structural configurations may cause very low critical galloping velocities. Additionally, the hypothesis of polar symmetry commonly used in technical calculations may lead to relevant underestimations of the wind-excited response. From this point of view, this paper provides possible interpretations for a number of damage and collapses of this structural type without clear and suitable explanations.